Brand Trust as a Determinant of Consumer Loyalty: An Empirical Study on Skincare Brands - Argya Willa Larasati; Didin Hikmah Perkasa (Manunggal Halim Jaya, 2026)
This study assesses the importance of brand trust in creating customer loyalty for ESQA, a premium cosmetics brand from Indonesia. The background of this research stems from the rapid growth of the beauty industry in this country, which is accompanied by fierce competition between local and international products. Therefore, it is necessary to identify the factors that influence consumer loyalty. A quantitative methodology was used by conducting an online survey of 100 female ESQA users in the Greater Jakarta area. Using simple linear regression, the analysis found that brand trust significantly influences consumer loyalty (R² = 0.725). This means that 72.5% of changes in consumer loyalty are closely related to the level of trust in the brand. These results confirm that consistency in product quality, transparency in communication, and brand credibility are important aspects for retaining consumers in the long term. Practical recommendations from this study highlight the need for local beauty industry players to implement sustainable brand management strategies to address market competition.